Design and development of A 3-Degree of freedom parallel manipulator / Lubabatu Baballe Ila - Lubabatu, Baballe Ila (2015)
Parallel manipulators have gained a lot of interest during the recent five decades. A parallel manipulator is constructed with an upper moving platform and a lower fixed platform, connected by at least two linkages in parallel, hence the name. Parallel manipulators have so many advantages over their serial counterparts. Some of these advantages are high accuracy, high stiffness and low inertia which make them favorable for numerous applications. Parallel manipulators also have several disadvantages such as high cost, small workspace, complex forward kinematics and complicated forms. To alleviate these disadvantages, the design and development of parallel manipulators with less than six degree of freedom was focused on by numerous researchers. In this paper, the focus is on 3-DOF parallel manipulators. A number of 3-DOF parallel mechanisms were compared and contrasted on the basis of type of configuration, workspace, stiffness and dexterity in order to choose the best manipulator. However, there is no criteria that can be used to choose the best parallel robot. It all depends on desired application. Here, a 3-RPS parallel manipulator was chosen for a massage application due to its proposed suitability for the task. Forward and Inverse Kinematics of the mechanism were studied. The mechanism was designed using CAD software. A prototype was built and analyzed. It has been found that the CAD software both predicted the output and the limitations of the mechanism. The system can be extended to motion platform once the dynamics equation is established.